Prediction of drug-drug plasma protein binding interactions of resveratrol in combination with celecoxib and leflunomide by molecular docking combined with an ultrafiltration technique - Zhou Peng; Hua Fang (Acta Pharmaceutica)
The present study is aimed at computational prediction of the molecular interactions between resveratrol, celecoxib, leflunomide and human serum albumin (HSA) and then investigates the plasma protein binding of resveratrol combined with celecoxib or leflunomide by an ultrafiltration technique. Molecular operating environment (MOE, 2008.10) software package was used to explore molecular interactions between the drugs and HSA. Molecular docking was adopted to predict the interactions between resveratrol and other drugs and then the ultrafiltration technique was used to verify the docking results. In in vitro experiments, a mixture of resveratrol and celecoxib or leflunomide was added to rat plasma for determination of the plasma protein binding rate. Molecular docking results have shown that resveratrol interacts with HSA mainly through hydrogen bond and π-π stacking, while celecoxib and leflunomide bind only with the hydrogen bond. Celecoxib or leflunomide, even at high tested doses, did not affect the plasma protein binding of resveratrol, thus suggesting pharmacological suitability of the investigated combinations.